2009
DOI: 10.1111/j.1600-0706.2009.17476.x
|View full text |Cite
|
Sign up to set email alerts
|

Geographic variation in sterilizing parasite species and the Red Queen

Abstract: The Red Queen hypothesis predicts that sexual reproduction should be favoured in locations where the risk of infection by virulent parasites is consistently high. When hosts are exposed to multiple parasites over their geographic range, the coevolving parasite species may vary among host populations. We surveyed 26 streams on the South Island of New Zealand to determine whether the frequency of snails (Potamopyrgus antipodarum) infected by various sterilizing trematode parasite species was correlated with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 36 publications
2
11
0
Order By: Relevance
“…Consistent with previous work (e.g., Lively and Jokela 2002;King and Lively 2009), we found that the frequency of sexual individuals increased with the prevalence of infection (Fig. 1A).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Consistent with previous work (e.g., Lively and Jokela 2002;King and Lively 2009), we found that the frequency of sexual individuals increased with the prevalence of infection (Fig. 1A).…”
Section: Discussionsupporting
confidence: 93%
“…The frequency of infection with the most common parasite was highly correlated with infection by all parasite species (Pearson correlation: r = 0.932, P < 0.001). However, in a previous study examining various measures of parasite-mediated selection, the frequency of the most common local parasite species was found to be the most appropriate (King and Lively 2009). Therefore, we used the infection frequency of the common parasite for all analyses.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent biogeographical studies of this snail have been consistent with earlier work, suggesting that asexual forms of the snail are more likely to occur in lakes and streams where parasites are rare (Lively, ; Lively & Jokela, ; King & Lively, ; King et al ., ). This pattern could, of course, be generated if males or sexual snails are, in general, inherently more susceptible to infection, but this is not the case (Vergara et al ., ).…”
Section: Tests Of the Red Queen Hypothesis Using Natural Populationsmentioning
confidence: 97%
“…, 2006; Hasu et al. , 2009; King & Lively, 2009). In particular, whether spatial variation in infection frequency is because of environmental factors, genetic variation for host resistance or a combination of both factors is still unresolved.…”
Section: Introductionmentioning
confidence: 99%